Evaluation of the molluscicidal properties of Euphorbia splendens var. hislopii (n. e. b.) (Euphorbiaceae) - 1: experimental test in a lentic habitat - Nelymar Martineli Mendes; Darcilio Fernandes Baptista; Maurício Carvalho de Vasconcellos; Virgínia Torres Schall (Memorias do Instituto Oswaldo Cruz, 1992)
The latex of Euphorbia splendens var. hislopii, at concentrations between 5 to 12 mg/l, kills 100% of the population of Biomphalaria glabrata in a lentic habitat, after 24 h. The lyophilized latex, stocked for 18 months, killed only 34.2% of the snails, at the concentration of 5 mg/l, and 96.0% at 12 mg/l. No lethal effect was observed among Pomacea haustrum exposed to the same concentrations of the molluscicide.